Yesterday's tomorrows and tomorrow's yesterdays: Utopian literary visions of Antarctic futures - Elizabeth Leane (2013)
This article surveys utopian visions of Antarctica’s future offered by literary texts in English. The “metaphorics of opposition” associated with Antarctica’s South Polar location has made it a popular site for literary utopias for centuries. Since the time-displaced utopia (or euchronia) began to flourish in the late nineteenth century, numerous literary speculations on the future of the continent have appeared. The article points out emergent patterns and repeated motifs within this subgenre. In early temporal utopias, Antarctica provides welcome space for imperial expansion and resource exploitation. In the dystopian, post-apocalyptic fiction that burgeoned after the Second World War, its icescape functions as both a possible threat and a place of refuge. The continent can be a source of hope in recent near-future fiction, although usually in an ambiguous manner. Literary visions of a future Antarctica inevitably extrapolate problems and opportunities evident in their authors’ own times. They provide estranged, denaturalized and hence potentially clearer perspectives on current issues: the present looks different seen as tomorrow’s yesterday.